1877. Discrepant Susceptibilities Have Minimal Impact on Antibiotic Prescribing for Patients With Two or More Blood Cultures Positive for Coagulase-Negative Staphylococci. (26th November 2018) - Smith, Jessica; Palavecino, Elizabeth; Beardsley, James; Johnson, James; Ohl, Christopher; Luther, Vera; Williamson, John
Abstract: Background: CoNS are common blood culture (BCx) contaminants resulting in unnecessary antibiotic therapy. Species reporting of CoNS is now possible in many medical centers due to new technology. When CoNS are isolated from multiple BCx, factors such as different susceptibility patterns and/or different species might suggest contamination. The purpose of this study was to characterize antibiotic usage attributable to CoNS positive BCx and to determine whether reporting of CoNS species could help reduce unnecessary antibiotics. Methods: Inpatients from January to June 2017 at our institution were screened retrospectively. During the study period, CoNS species were not reported (except S. lugdunensis ). Patients (patients) ≥18 years old with ≥1 BCx positive for CoNS were included. Patients who were neutropenic, treated with staphylococcal antibiotics (SAbx) for a non-CoNS infection, or treated for CoNS with an antibiotic other than the defined SAbx were excluded. Patients were categorized into pre-defined groups: single positive BCx(Group 1), ≥2 positive BCx with different (Group 2) or same (Group 3) susceptibilities. A random sample of patients was screened until 50 Group 1 patients met study criteria. Additional data were collected on all remaining Group 2 and 3 patients in the study period, including species name obtained from laboratory database. The primary outcome was attributable use of SAbx among patients in each group. Additional analyses were performed to compare the use of SAbx among Groups 2 and 3. Results: One hundred two patients were included. In the random sample ( n = 76), 34% had ≥2 positive BCx. S. epidermidis was isolated more frequently in Groups 2 and 3 than in Group 1 (69% vs. 52%, P = 0.03). 74% of patients received at least 1 SAbx (97% vancomycin). Attributable use of SAbx was greater among Groups 2 and 3 ( P < 0.001, figure). Differing susceptibilities occurred in 24/52 (46%) patients but did not impact SAbx use ( P = 0.57 for DOTs, P = 0.35 for DDDs). Seventeen (33%) of patients with ≥2 positive BCxhad different species. Conclusion: Significantly more SAbx were prescribed when ≥2 BCx were positive for CoNS. Since differences in susceptibilities has little effect, future studies should evaluate the impact of reporting CoNS species on appropriate antibiotic prescribing. * P < 0.001 for Group 1 vs. 2 and Group 1 vs. 3 (DOTs and DDDs). P = NS for Group 2 vs. 3. Disclosures: All authors: No reported disclosures.